Pengaruh Ketersediaan Fasilitas Ruang Tunggu Terminal Domestik Terhadap Kepuasan Penumpang Di Bandar Udara Internasional Yogyakarta - Sri Banun Juliati; Eny Sri Haryati (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2023)
Waiting room service at YIA airport is very important for passengers. With good service facilities, good service will be created, so that foreign and domestic passengers will be impressed. For this reason, in serving the needs of the community in air transportation services, it is necessary to pay attention to the service and the provision of maximum facilities. The provision of these facilities is expected to have an impact on passenger satisfaction. The purpose of this study was to determine the effect of domestic waiting room facilities on Yogyakarta International Airport passenger satisfaction and to determine how much influence domestic waiting room facilities had on Yogyakarta International Airport passengers. This research used a quantitative method using a purposive sampling technique. The sample used was 100 respondents, the results of distributing questionnaires to 100 respondents who used the domestic terminal waiting room facilities at Yogyakarta International Airport and were measured using the slovin formula. Retrieval of data on the number of samples using a survey with an instrument in the form of a questionnaire. Data were analyzed using simple linear regression, T test and coefficient of determination with the availability of domestic terminal waiting room facilities as the independent variable and passenger satisfaction as the dependent variable which were processed using the SPSS application Version 26.0. The results showed that the t count > t table with a value of 50.871 > 1.661 with a significant level of 0.05, so it can be concluded that Ho is rejected and Ha is accepted, which means that the influence of the availability of waiting room facilities on passenger satisfaction at Yogyakarta International Airport is partially accepted. The percentage based on the coefficient of determination test shows that the R square is 0.964. This means that the effect of the availability of waiting room facilities on passenger satisfaction at Yogyakarta International Airport is 96.4%.